Bowtie slotted dual‐band SIW antenna. Issue 10 (27th July 2016) - Nandi, Sourav; Mohan, Akhilesh
ABSTRACT: A dual‐band substrate integrated waveguide (SIW) antenna with bow‐tie shaped slot and two conducting via‐holes within the cavity is presented in this paper. The bow‐tie shaped slot introduces strong capacitive loading effect, which brings down the TE210 mode of the cavity from 11.08 GHz to 10.3 GHz and the first band of the antenna with 4.94% impedance bandwidth is generated. Another two higher order hybrid modes, generated by incorporating two metallic via‐holes, are tuned and merged together by properly optimizing the diameter and position of those two via‐holes to obtain the second band of the antenna with comparatively large −10 dB impedance bandwidth of 7.14%. Peak realized gains obtained at both of the frequency bands are more than 5.23 dBi. The simulated and measured results are compared and they are in good agreement. The physical size of the proposed antenna is 22 mm × 32 mm × 0.787 mm. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2303–2308, 2016